Post-traumatic stress disorder: the development of effective psychological treatments. - Ehlers, A; Clark, D (2008)
Post-traumatic stress disorder (PTSD) has only relatively recently been introduced into the diagnostic classification of mental disorders. Building on advances in the treatment of other anxiety disorders, a range of effective psychological treatments for PTSD has been developed. The most effective of these treatments focus on the patient's memory for the traumatic event and its meaning. This paper briefly reviews the currently available evidence for these treatments. It then illustrates the process of developing effective psychological treatments by discussing how a combination of phenomenological, experimental and treatment development studies, and theoretical considerations was used to develop a trauma-focused cognitive-behavioral treatment, cognitive therapy (CT) for PTSD. This treatment program builds on Ehlers and Clark's (2000) model of PTSD, which specifies two core cognitive abnormalities in PTSD. First, people with chronic PTSD show idiosyncratic personal meanings (appraisals) of the trauma and/or its sequelae that lead to a sense of serious current threat. Second, the nature of the trauma memory explains the occurrence of re-experiencing symptoms. It is further proposed that the idiosyncratic appraisals motivate a series of dysfunctional behaviors (such as safety-seeking behaviors) and cognitive strategies (such as thought suppression and rumination) that are intended to reduce the sense of current threat, but maintain the problem by preventing change in the appraisals and trauma memory, and/or lead to increases in symptoms. CT addresses the cognitive abnormalities and maintaining behaviors in an individualized, but focused, way. Four randomized controlled trials and two dissemination studies showed that CT for PTSD is acceptable and effective.